Physical assessment of tortures: Interobserver analysis of medico-legal degrees of consistency based on the Istanbul protocol. (May 2023) - Franceschetti, Lorenzo; Magli, Francesca; Nava, Chiara; De Angelis, Danilo; Verzeletti, Andrea; Cattaneo, Cristina
Highlights: The medico-legal assessment of physical violence is crucial. The medico-legal limits are important and well-known by practitioners. The Istanbul Protocol's invitation to a multidisciplinary approach is desirable. The correct assessment of injuries guarantees a proper and consistent help for refugees. Abstract: The Istanbul Protocol section on medicolegal evaluation delineates the guidelines for the correct management of the physical examination and the methods of assigning the degrees of consistency. Considering that most cases exhibit highly heterogeneous lesions, the examiner is forced to rely on his own experience, and their evaluation may be very subjective. The purpose of this work is to understand how subjective such an evaluation may be and whether the "experience" factor, interpreted as years dedicated to this profession and the number of cases evaluated, is statistically significant. To this end, a survey containing eleven cases of pre-evaluated asylum seekers was sent to thirty Italian clinical forensic practitioners. The participants were invited to assign a degree of consistency to each case according to the Istanbul Protocol guidelines, besides answering a few questions regarding their professional record. The doctors were divided into groups based on the number of cases evaluated and the experience collected expressed in years, and then interobserver analysis was performed. Results showed that the Fleiss' Kappa coefficient acquired significant values when attention was turned to the sub-samples composed of more experienced participants. Therefore, the introduction of appropriately trained health professionals – "experts in migrations and torture" – could lower the risks of misinterpretation and make the assessment as reproducible as possible.